2010
DOI: 10.1021/es902714u
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management System (ISO 14001) Certification in Developing Countries: Challenges and Implementation Strategies

Abstract: ISO standards are voluntary, but acquiring their certification can evolve from a marketing advantage into an “industry standard” necessary for fruitful competitiveness. The cost associated with certification and a lack of coherent national/regional policies can therefore put companies in developing countries at a significant disadvantage in the global marketplace. Since the ISO 14000 category addresses the reduction of environmental footprint(s) and waste production, such companies have less ability to adopt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 27 publications
(28 reference statements)
0
47
0
4
Order By: Relevance
“…The absence of pressure by key social sectors like local communities, media, NGOs, banks, insurance companies or politicians may not provide the necessary push for companies to eco-innovate. Massoud et al (2010) found out the various barriers which hinder the implementation of ISO 14001 and Environment Management System (EMS) in Lebanese food industry. These barriers are: time demand, lack of knowledge, lack management priority, cost of certification, lack of customer demand, not required for export, lack of government support, benefits not clear, not legal requirement and lack of government supports.…”
Section: Literature Review For Barriers Of Gscmmentioning
confidence: 99%
“…The absence of pressure by key social sectors like local communities, media, NGOs, banks, insurance companies or politicians may not provide the necessary push for companies to eco-innovate. Massoud et al (2010) found out the various barriers which hinder the implementation of ISO 14001 and Environment Management System (EMS) in Lebanese food industry. These barriers are: time demand, lack of knowledge, lack management priority, cost of certification, lack of customer demand, not required for export, lack of government support, benefits not clear, not legal requirement and lack of government supports.…”
Section: Literature Review For Barriers Of Gscmmentioning
confidence: 99%
“…Interestingly, for each individual supplier, the average scores for these three groups of clusters are all approximately the same with a maximum difference of 0.6 only (for Supplier A) and almost the same scores for Supplier C (2.42, 2.42, and 2.46). A similar link was also identified by Wong et al [4] in studying 122 manufacturing firms investigating the role of environmental management capabilities in achieving green operation (GO) at the manufacturing level; Lo et al [17] also studied the role for proper environmental management systems (EMSs) in controlling the environmental performance of manufacturing firms, particularly in developing countries where the implementation of such EMSs faces challenges such as lack of appropriate infrastructure, efficient policies and effective environmental regulations, and financial resources [40]. …”
Section: Connection Between Three Groups Of Clustersmentioning
confidence: 61%
“…Others added that policies and standards should complete each other because they both have common goals and should work in parallel. Generally, the lack of appropriate infrastructure, unsound policies, and ineffective environmental regulations as well as financial and human resource constraints are the major challenges facing developing countries in implementing environmental management practices [11].…”
Section: Challenges Of Implementing Environmental Management Practicesmentioning
confidence: 99%